Andrew Malkinson: A miscarriage of justice?. (April 2022) - Samuels, Alec
In the case of Andrew Malkinson, a number of concerning or disturbing features about the conduct of the case by all involved have emerged. Application is therefore being made to the Criminal Cases Review Commission to reconsider and refer the case.